2021
DOI: 10.25301/jpda.303.209
|View full text |Cite
|
Sign up to set email alerts
|

Root Canal Configuration of the Maxillary Second Permanent Molars in Pakistani Subpopulation

Abstract: OBJECTIVE: The aim of the study is to assess the variations in the root canal configuration of maxillary second permanent molars in the Pakistani subpopulation by using different clinical aids in vivo. METHODOLOGY: The Cross-sectional analytical study was conducted from April to October 2018 at the College of Dentistry, Riphah International University, Pakistan. The root canal configurations of Maxillary second molars were evaluated in 95 adult patients that presented to the Operative Department, after obtaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…This difference in findings might have been because that study was conducted in vitro and did not involve the use of CBCT imaging. 40 Similarly, in another study conducted on an Indian pediatric population, 20% of permanent MFM had MB2 canals. 36 Studies conducted on the RCS morphology of MSM in different populations have yielded varying results.…”
Section: Discussionmentioning
confidence: 91%
“…This difference in findings might have been because that study was conducted in vitro and did not involve the use of CBCT imaging. 40 Similarly, in another study conducted on an Indian pediatric population, 20% of permanent MFM had MB2 canals. 36 Studies conducted on the RCS morphology of MSM in different populations have yielded varying results.…”
Section: Discussionmentioning
confidence: 91%
“…This allowed thorough disinfection of the canal space by effectively eliminating all the niches where bacteria may reside [ 10 , 11 ]. Only single-rooted teeth were included in order to eliminate the impact of varied and complex root canals systems encountered in multi-rooted teeth [ 12 , 13 , 14 , 15 , 16 ]. This study revealed information regarding the relative effectiveness of different intra-canal medicaments in alleviating post-operative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Profound knowledge of root canal anatomy is a basic prerequisite for successful root canal treatment. [1][2][3][4] This understanding of both preoperative and intraoperative evaluation of atypical anatomy, aids the clinician in locating and cleaning canals efficiently. 5 It was thought that single rooted teeth had single canals like mandibular incisors.…”
Section: Introductionmentioning
confidence: 99%